2012
DOI: 10.1007/s11033-012-2212-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis following olfactory learning in Apis mellifera

Abstract: The honeybee has a strong learning and memory ability, and is recognized as the best model organism for studying the neurobiological basis of learning and memory. In this study, we analyzed the gene expression difference following proboscis extension response-based olfactory learning in the A. mellifera using a tag-based digital gene expression (DGE) method. We obtained about 5.71 and 5.65 million clean tags from the trained group and untrained group, respectively. A total of 259 differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 42 publications
7
30
0
Order By: Relevance
“…Our findings are in agreement with recent studies that show there is a general downregulation of protein-coding genes and upregulation of miRNAs associated with learning and memory in honeybees 34,35 . These studies report genes involved with cytoskeleton organization, as well as lipid, protein and glucose metabolism are downregulated, and six out of the seven miRNAs reported upregulated in our study after learning were also found upregulated in their work 35 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are in agreement with recent studies that show there is a general downregulation of protein-coding genes and upregulation of miRNAs associated with learning and memory in honeybees 34,35 . These studies report genes involved with cytoskeleton organization, as well as lipid, protein and glucose metabolism are downregulated, and six out of the seven miRNAs reported upregulated in our study after learning were also found upregulated in their work 35 .…”
Section: Discussionsupporting
confidence: 94%
“…This observation was also made by previous studies using both olfactory 34 and visual 35 learning paradigms in honeybees. Similarly in mammals, there is a pronounced downregulation of gene expression 24 h after long-term-potentiation (LTP) induction, which appears to be partially mediated via timedependent regulation of miRNA expression 45 .…”
Section: Discussionsupporting
confidence: 83%
“…Among the DEGs discovered in these studies was a GABA receptor (Qin et al, 2014;Wang et al, 2013). Ionotropic GABA receptors in the MB calyces are crucial for reversal learning, but not extinction or discriminatory learning in general (Boitard et al, 2015).…”
Section: Memory-associated Genesmentioning
confidence: 99%
“…1.2). Changes in gene transcription Menzel et al, 2001;Friedrich et al, 2004;Lefer et al, 2013;Qin et al, 2014;Wang et al, 2013;Cristino et al, 2014), translation Friedrich et al, 2004;Stollhoff et al, 2005) and protein degradation (Felsenberg et al, 2012(Felsenberg et al, , 2014 are all crucial for memory formation. Here I will particularly focus DNA methylation and memory formation in bees on transcription and its role in memory formation.…”
Section: Molecular Mechanisms Of Honey Bee Memory Formationmentioning
confidence: 99%
See 1 more Smart Citation